KESESUAIAN IKLIM TERHADAP TANAMAN KOPI ROBUSTA (Coffea Canephora) DI KABUPATEN TANAH DATAR - mufti khairatunnisa; Yudi Antomi (JURNAL BUANA, 2021)
This study aims to determine :1) Climate classification in Tanah Datar Regency according to Schmidt and Ferguson systems 2) The suitability of each type of climate to the growth of robusta coffee plants. This type of research is classified as quantitative research aimed at finding the relationship between each variable so as to produce new information by revealing or describing something that already exists or is currently ongoing. Data collection uses secondary data obtained from the BMKG Meteorology, Climatology and Geophysics Agency and the Tanah Datar Central Statistics Agency. The results of this study indicate that the climate type of Tanah Datar Regency based on the 2015-2019 rainfall in each rain post according to the affordability of the Batipuh rain station is included in very wet climate types and other rain posts are included in the wet climate type. Tanah District is included in a suitable area for coffee plant growth because it is supported by weather elements such as rainfall, air humidity, air temperature, and altitude., With an area that is included in the very suitable category of 34%, the appropriate category is 42%, and for quite suitable category 25%